INTEGRATED APPROACH FOR IMPROVING ENGLISH COMPETENCY AND LEARNING ENCOURAGEMENT FOR NON-ENGLISH MAJOR STUDENTS - Samsul Amri; Syafrizal Syafrizal (INOVISH JOURNAL, 2020)
At the Higher Education level, English as a General Subject acts as recognition for the primary focuses learning experience. Using these language skills and components, learners are not trained sufficiently. It causes many circumstances, such as poor performance, limited vocabulary, keen learning interest, a short amount of practice, and more. The requirement for teaching quality is that they can apply English as a medium of communication. The researchers offer a workable solution by adjusting the Integrated Approach to overcome this issue. Thus, the current research objectives are to determine the students' improvement, instruction process, and the influencing factors on their language abilities and motivational beliefs. It is designed as an Action Research. Accounting Major students, which consist of 37 students, are the participants of this research. Tests, observations, and interviews were included in the data gathering process. Then the findings reveal that 13.5 percent of students earned top grades. 40.5 percent of students got decent grades. However, there are already participants who obtained a sufficient level (32.5 percent) and less (13.5 percent). It finds that the Integrated Approach enables improving their English competence and learning motivation through the process of socializing, evaluating, controlling, assisting, and practicing. Furthermore, their improvement factors cover students' motivation, teaching approach, and lecturers' role. It illustrates progress in the learning process made by them. Eventually, this offers evidence that the Integrated Approach implementation favors optimizing their English ability and learning encouragement.